(untitled) (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2019)
Several votive terracottas have been found near the "semicircular base". There are no elements that allow the identification of the divinity recipient of the cult. The typology of the ex voto and the topographical location, however, suggest a health-related cult, linked to fertility or rites of passage and purification. Even dating is not sure. However, votive materials span over a wide chronological period (VI-II century BC) and show a long continuity of use.